Maternal Serum Fractalkine Concentrations in Pregnancies Complicated by Fetal Growth Restriction - Toprak Sager , Ecem Berfun; Kale, Ibrahim; Sager, Hakan; Ozel, Aysegul; Muhcu, Murat (Gynecology Obstetrics & Reproductive Medicine, 2023)
OBJECTIVE: Fractalkine is a newly discovered chemokine that is expressed in placental tissue during pregnancy and is subsequently shed into the maternal serum. Although there are a few studies examining the relationship between fractalkine and preeclampsia, its role in isolated fetal growth restriction has not been investigated yet. In this study, we aimed to investigate the relationship between isolated fetal growth restriction and maternal serum fractalkine concentrations. STUDY DESIGN: This cross-sectional study was conducted on 86 pregnant women, 25 of whom were diagnosed with fetal growth restriction in the third trimester, 23 were small for gestational age, and 38 were healthy controls. These three groups were compared in terms of maternal serum fractalkine concentrations. RESULTS: While the highest mean maternal serum fractalkine concentration was found in the small for gestational age group at 23.31 ng/mL, it was determined as 18.06 ng/mL in the fetal growth restriction group and 16.03 ng/mL in the control group. We did not find a statistical difference between the groups in terms of fractalkine concentrations (p=0.258). When the patients with fetal growth restriction and small for gestational age were evaluated as a single group and compared with the control group, the mean fractalkine concentration in the fetal growth restriction+small for gestational age group was higher than the control group, but this difference was not statistically significant (p=0.214). CONCLUSION: Maternal serum fractalkine concentration was higher in both fetal growth restriction and small for gestational age groups compared to healthy controls, but this difference was not statistically significant. The role of the fractalkine molecule in the development of fetal growth restriction remains to be clarified in future studies with larger series.